Evaluation of Two Readings for the QuicGM Aspergillus Lateral Flow Assay in a Group of Immunocompromised Patients in Iraq - Kareem, Hiba S.; M. Al-Wattar, Wifaq (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Aspergillus spp. causes a wide range of diseases called Invasive Aspergillosis (IA) which is a fatal illness that affects a variety of immunocompromised people worldwide.Objective: Using the lateral flow test for the detection of Galactomannan antigen in immunocompromised patients suspected to have IA.Methods: This study was conducted on 72 patients, whose samples (serum, Bronchoalveolar lavage, Blood) were collected from the Hematology-Oncology Unit at Baghdad Teaching Hospital and Pediatric Welfare Hospital, and ICU in Ghazi AL-Hariri Surgical Specialties Hospital, Bone Marrow Transplantation Center in the period between November 2022 to February 2023. Patients’ blood and sputum were sent for fungal culture to confirm the diagnosis in most cases.Results: QuicGM Aspergillus Lateral Flow Assay was conducted on 72 patients, of whom 34 (47.2%) were positive and 38 (52.7%) were negative (P-values of 0.001 and 0.5) respectively. This screening aimed at detecting IA. One week later, the second confirmative result was obtained from 24 patients to determine the response to antifungal drugs or recovery from neutropenia of which 15 readings were negative and nine were positive. Out of 48 single readings, 25 were positive and 23 were negative. All 72 members of the control group gave negative results. This study is the first in Iraq to use this assay.Conclusion: QuicGM Aspergillus Lateral Flow Assay was found to be reliable, sensitive, and specific, and proved to be a very good guide for the early diagnosis of IA in immunocompromised patients and in monitoring treatment outcomes and follow-up.